The Influence of Human Development Index and Gross Regional Domestic Product on Poverty in Medan City With Zakat Funds As a Moderation Variable - Fadila, Sheila; Arif Lubis, Fauzi; Syahriza, Rahmi (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This research aims to determine the influence of the Human Development Index (HDI) and Gross Regional Domestic Product (GRDP) on poverty in Medan City, with zakat funds as a moderating variable. The research method uses a quantitative approach with the help of the Eviews 9 program. Secondary data was obtained from the Central Statistics Agency (BPS) and BAZNAS in Medan. The research results show that: HDI has no effect on poverty, GRDP has no effect on poverty, HDI and GRDP have an effect on poverty, zakat funds can moderate the relationship between HDI and poverty, zakat funds can moderate the relationship between GRDP and poverty, and zakat funds can moderate the relationship between HDI, GRDP and poverty.